Basic of Learning Theory: (Behaviorism, Cognitivism, Constructivism, and Humanism) - Muhajirah Muhajirah (Research and Education Development (READ) Institute collaborate with Faculty of Education and Teacher Training of IAIN Palopo, 2020)
In general, the term learning is understood as the teacher's conscious effort to help students so that they can learn according to their interests and needs. The more aware and professional a teacher is in educating, the better the quality of students and vice versa. Another term that is combined with learning in this article is theory. In a general sense, the method is often associated with a set of concepts, ideas, and procedures that can be learned, analyzed, and verified. So, learning theory is a collection of thoughts, ideas, systems in which how to practice the learning process between teacher and student and other elements related to learning activities. Learning theory itself can be interpreted as a theory that contains procedures for how a teacher applies teaching and learning activities, which will later be used to students both inside and outside the classroom.